Neurotoxins and Their Binding Areas on Voltage-Gated Sodium Channels - Stevens, Marijke; Peigneur, Steve; Tytgat, Jan (Frontiers in Pharmacology, 2011)
Voltage-gated Sodium Channels (VGSCs) are large transmembrane proteins that conduct sodium ions across the membrane and by doing so they generate signals of communication between many kinds of tissues. They are responsible for the generation and propagation of action potentials in excitable cells, in close collaboration with other channels like potassium channels. Genetic defects in sodium channel genes therefore can cause a wide variety of diseases, generally called ‘channelopathies’. The first insights into the mechanism of action potentials and the involvement of sodium channels originated from Hodgkin and Huxley for which they were awarded the Nobel Prize in 1963. Until now, these concepts still form the basis for understanding the functioning of VGSCs. When VGSCs sense a sufficient change in membrane potential, they are activated and will generate a massive influx of sodium ions. Immediately after, channels will start inactivating and currents decrease. In the inactivated state channels stay refractory for any new stimulus and they must return to the closed state before being susceptible to any new depolarization. On the other hand, studies with neurotoxins like tetrodotoxin (TTX) and saxitoxin (STX) also contributed largely to our today’s understanding of the structure and function of ion channels and specifically of VGSCs. Moreover, neurotoxins acting on ion channels turned out to be valuable tools in the development of new drugs for the enormous range of diseases in which ion channels are involved. A recent example of a synthetic neurotoxin that made it to the market is ziconotide (Prialt®, Elan). The original peptide, -MVIIA, is derived from the cone snail Conus magus and now FDA/EMEA-approved for the management of severe chronic pain by blocking the N-type voltage-gated calcium channels in neurons. This review focuses on the current status of research on neurotoxins acting on VGSC, their contribution to further unravel the structure and function of